Critical Success Factors (CSFs) of construction project management from the perspective of project managers / Qanish Aizet Affendi and Kartina Alauddin - Affendi, Qanish Aizet; Alauddin, Kartina (2023)
Developing countries rely heavily on the construction sector to implement their long-term development plans. Certain factors are more critical than others in project success. Successful construction project greatly depends on how the project has been managed and controlled. Once critical success factors have been identified, it is likely to achieve the project success. Therefore, this research aim is to identify the Critical Success Factors (CSFs) of construction projects management (CPM) from the perspective of project managers. The objective of this research is to identify the CSFs of the construction project management implementation in construction projects and to determine the key factors of CSFs in assisting the project manager in managing the construction projects in Perak. The research identifies eleven factors which are critical in the CPM. The findings also indicated that effective communication was the most critical in CPM. To achieve success in construction projects, improving communication skills can assist the construction project manager in managing the construction projects.